The Meaning of "Participation" in Co‐Design with Children and Youth: Relationships, Roles, and Interactions. Issue 1 (13th October 2021) - Bowler, Leanne; Wang, Karen; Lopatovska, Irene; Rosin, Mark
Abstract: The paper examines the concept of participation in co‐design practices with children and youth. Rooted in Participatory Design and Participatory Action Research frameworks, the paper draws from multi‐disciplinary literature to survey existing definitions of the relationships, roles, and types of human interactions in participatory co‐design. The paper advocates for the active role of children and youth in the co‐design process and presents models of youth participation. The paper highlights the importance of understanding and clearly communicating various degrees of participation, with the ultimate goal of empowering youth and involving them in brainstorming, planning, decision‐making, and interpretation stages of the design process. We introduce the concept of conscious co‐design and the need to reflect on the design process at a meta level in Participatory Design and Participatory Action Research .